A study of differential foundation settlement of piled raft and its effect on the long‐term vertical shortening of super‐tall buildings. (8th January 2021) - Wang, Lilin; Zhao, Xin; Liu, Shehong
Summary: In this study, the long‐term differential foundation settlement and vertical shortening of super‐tall buildings are investigated considering the coupling effect. At first, a time‐dependent settlement model is proposed to predict the foundation settlement based on the construction sequence method, in which both soil compression and pile shortening are considered. The pile shortening including the elasticity, shrinkage, and creep contributes to the most settlement of a single pile. The distribution of foundation settlement of piled raft is pot shaped with a large value in the core while small values in the surroundings. A time‐dependent soil‐foundation‐structure system is then developed using a series of equivalent springs to represent the distributed foundation settlements, by which the vertical shortenings of shear wall and mega column are predicted considering the coupling effect and moisture distribution. The pot‐shaped distribution of foundation settlement of piled raft leads to the decrease of vertical shortening for shear wall while the increase of vertical shortening for mega column, especially in the low stories. Finally, some health monitoring records of the Shanghai Tower are applied to validate the proposed time‐dependent settlement model and soil‐foundation‐structure system. The predicted foundation settlements show reasonable agreement with the monitoring records. The predicted vertical shortenings with considering the differential foundation settlement agree better with measurements than those without considering the differential foundation settlement.